Psychological and Educational Challenges of Immigrant Adolescents in Italy: Exploring Mental Health, Life Satisfaction, Student–Teacher Relationship, and Academic Disparities - Valeria Cavioni; Elisabetta Conte; Veronica Ornaghi (Adolescents)
Adolescence is a critical stage marked by identity formation and social challenges, especially for adolescents with migratory backgrounds who must reconcile their ethnic identities with the dominant culture. This study explores the mental health, life satisfaction, student–teacher relationship, and academic achievement of Italian-born, second-generation, and first-generation immigrants. The sample of 680 adolescents (M = 382; F = 280; Prefer not to say = 18; Mean age = 16.77 years) includes native-born Italians (n = 244), second-generation immigrants (n = 210), and first-generation immigrants (n = 226). Data were collected using self-report measures for mental health, life satisfaction, student–teacher relationship, and school achievement. A Multivariate Analysis of Variance identified significant group differences, followed by post-hoc tests to further explore differences between the groups. Second-generation immigrants reported significantly lower emotional well-being compared to their Italian-born peers. Both first- and second-generation immigrants exhibited lower life satisfaction, particularly in peer relationships. In terms of student–teacher relationship, second-generation immigrants perceived higher levels of school danger compared to Italian-born adolescents, possibly driven by discrimination. Academic outcomes revealed significant disparities, with Italian-born students outperforming second-generation immigrants, highlighting the impact of acculturative and bicultural stress. The findings highlight the unique challenges second-generation immigrants face in Italy in balancing cultural integration with preserving their heritage.